2020
DOI: 10.1038/s41598-020-78016-8
|View full text |Cite
|
Sign up to set email alerts
|

BRCAness as a prognostic indicator in patients with early breast cancer

Abstract: BRCAness is defined as a phenotypic copy of germline BRCA mutations, which describes presence of homologous recombination defects in sporadic cancers. We detected BRCAness by multiplex ligation-dependent probe amplification (MLPA) and explored whether BRCAness can be used as a predictor of prognosis. BRCAness status was classified for total 121 breast cancer patients. Forty-eight patients (39.7%) were identified as BRCAness positive. Tumors of BRCAness were more likely to be hormone receptors negative (95.8% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…BRCA1 and BRCA2 are tumor suppressor genes with a fundamental role in DNA repair through the homologous recombination pathway [61]. Germline mutations in these genes are associated with an increased risk of developing breast and ovarian cancer [62], with the mean cumulative breast cancer risk at 80 years of age for BRCA1 and BRCA2 genes being 72% and 69%, respectively [3].…”
Section: P53mentioning
confidence: 99%
“…BRCA1 and BRCA2 are tumor suppressor genes with a fundamental role in DNA repair through the homologous recombination pathway [61]. Germline mutations in these genes are associated with an increased risk of developing breast and ovarian cancer [62], with the mean cumulative breast cancer risk at 80 years of age for BRCA1 and BRCA2 genes being 72% and 69%, respectively [3].…”
Section: P53mentioning
confidence: 99%
“…For instance, somatic mutations of homologous recombination repair (HRR) genes such as ATM, ATR, PALB2 and RAD51 cause BRCAness [ 3 ]. BRCAness was reported to predict response to anticancer agents [ 4 ]. Since poly ADP-ribose polymerase (PARP) is also essential in DNA repair, PARP inhibitors (PARPis) cause synthetic lethality in tumors with BRCA1 and/or BRCA2 germline mutations and are used for ovarian, prostate, pancreatic, and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In NACT subgroup analysis, clinical response rate for taxane-based regimen was significantly lower in BRCAness patients (58.3% vs. 77.8%, p = 0.041). Authors concluded that BRCAness may suggest resistance to taxane-based CT [134]. Similarly, in the just above-mentioned study [133] the 50% inhibitory concentration of docetaxel was higher in BRCA mutant and BRCAness cell lines than their counterparts.…”
Section: Brcanessmentioning
confidence: 85%